KASUS VINA PEMERKOSAAN DAN PEMBUNUHAN : TINJAUAN HUKUM DAN KEADILAN BAGI KORBAN - Ihda Shofiyatun Nisa'; Ghufron Maulana Fatih (Jurnal Hukum Lex Generalis, 2023)
Abstract: The incident of sexual violence and murder involving Vina highlights numerous challenges in law enforcement and the pursuit of justice for victims. This article examines the legal dimensions of the case by analyzing relevant regulations pertaining to sexual violence and murder, while assessing the effectiveness of the legal system in delivering equitable justice. Utilizing a normative approach and case studies, the article underscores the significance of both retributive and restorative justice in addressing the complexities surrounding sexual violence, as well as its repercussions for victims and society as a whole.